Characterization of evolutionary changes in hemagglutinin of influenza H1N1 virus: a computational analysis - Rehman, Zaira (Virusdisease, 2016)
Influenza virus continues to evolve due to changes in the genome and the new strain of virus is more pathogenic then the previous strain. These changes may also help the virus to cross specie barrier and may also affect the binding pattern of virus.The main theme of the current study is the identification of changes in the hemagglutinin sequence of H1N1 virus from 1960 to 2011 and also how these changes affect the binding properties of virus. From 1960 to 2000 following important changes were observed: Ala198Asp and Gly225Glu in 1980; and Gly225Asp in 1999. From 1999 to 2011 many changes were observed, most of the changes were transient, but two of the changes, Gly225Asp and Ala227Glu, were consistent in the period of 1999–2010. These residues make the binding stronger. The important conserved residues are Asp190, Tyr98, His183 and Gln226. The current study will provide an understanding how virus evolve with the passage of time. The current study also helps to understand the changes in the binding pattern of virus. It will also help for the identification of new therapeutic targets. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13337-015-0294-4) contains supplementary material, which is available to authorized users.